A Multifaceted Action of Phytochrome B in Plant Environmental Adaptation - Kim, Jae Young; Lee, June-Hee; Park, Chung-Mo (Frontiers in Plant Science, 2021)
Light acts as a vital external cue that conveys surrounding information into plant growth and performance to facilitate plants to coordinate with changing environmental conditions. Upon exposure to light illumination, plants trigger a burst of molecular and physiological signaling cascades that induces not only photomorphogenic responses but also diverse adaptive behaviors. Notably, light responses and photomorphogenic traits are often associated with plant responses to other environmental cues, such as heat, cold, drought, and herbivore and pathogen attack. Growing evidence in recent years demonstrate that the red/far-red light-absorbing phytochrome (phy) photoreceptors, in particular phyB, play an essential role in plant adaptation responses to abiotic and biotic tensions by serving as a key mediator of information flow. It is also remarkable that phyB mediates the plant priming responses to numerous environmental challenges. In this minireview, we highlight recent advances on the multifaceted role of phyB during plant environmental adaptation. We also discuss the biological relevance and efficiency of the phy-mediated adaptive behaviors in potentially reducing fitness costs under unfavorable environments.